Swedish-Yiddish-Swedish Dictionary - Hessel, Jean (Institute for Language and Folklore, 2022)
Yiddish-Swedish-Yiddish Dictionary contains around 8200 entries. It contains three parts: one Swedish-Yiddish part, one Yiddish-Swedish part where the search words are indexed according to the Hebrew alphabet and lastly one transcribed Yiddish-Swedish part where the searchwords follow a phonetical pronouncation according to the Swedish alphabet.

Jiddisch-svensk-jiddisch-ordboken innehåller omkring 8 200 uppslagsord. Den består av tre delar: en svensk-jiddisch del, en jiddisch-svensk del där sökorden följer det hebreiska alfabetet och en transkriberad jiddisch-svensk del där sökorden följer uttalet utifrån det svenska alfabetet.
Svensk-jiddisch-svensk ordbok
Keywords: minority languages; minoritetsspråk; languages; språk; yiddish; jiddisch; national minority languages; nationella minoritetsspråk; dictionary; ordbok; Natural Language Processing; Språkbehandling och datorlingvistik